(3JaSjQ GdbQBf GdYXjes - (3YHO GdQMef Hf eMeO Hf EOQjS Hf GdefPQ GdJejej GdMfXdqj GdQGRqj, CHh eMeO , GHf CHj MGJe GdQGRj ,J (B327 (3g` s
(3ChdgG (B:s
(3dGMhd hdG bhI EdG HGddg hUdi Gddg Ydi SjOfG eMeO bGd GdTjN GdGeGe CHj MGJe YHO GdQMef GdOGfi(B: s
(3BNQgG (B:s
(3Je GdLRA GdChd ef cJGH JaSjQ CHj MGJe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B35s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B15) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs